The Impact of Corporate Social Responsibility Disclosure and Company Size on Company Financial Performance: The Role of Intellectual Capital as Moderating Variable - Atiqah, Atiqah; Akbari, Prillya Nurul; Rahma, Yusro (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This research aimed to examine the effect of CSR disclosure and company size on the Company's financial performance with intellectual Capital as a moderator. The population in this research are manufacturing companies registered for the 2019-2021 period. The research sample was determined using a purposive sampling method. MRA (Moderated Regression Analysis) was used to answer the hypothesis. This research indicates that CSR disclosure has a positive effect on the Company's financial performance, company size does not affect economic performance, and intellectual Capital has a positive impact on financial performance. Intellectual Capital can moderate the effect of CSR Disclosure on financial performance, and intellectual Capital can moderate the impact of company size on company financial performance. The novelty of this research is to include intellectual Capital as a moderator that strengthens the influence of CSR disclosure and company size on financial performance. The implication of this research is beneficial for the sustainability of the Company, which means that to improve the Company's financial performance, it must have qualified intellectual Capital to encourage CSR disclosure which will also have an impact on increasing the size of the Company.